Salmonella in Food Environments in Canteens: A Focus on Antibiotic and Disinfectant Resistance Patterns: Food related areas and food handlers in canteens were analysed for Salmonella - Pamuk, Şebnem; Erdoğan, Metin; Yıldırım, Yeliz; Ertaş Onmaz, Nurhan (Progress in Nutrition, 2022)
The objective of this study was to determine the molecular characterization and antibiotic and disinfectant resistance potential of Salmonella isolates from food related areas in canteens.This study was performed in food related areas as well as food handlers in student canteens in University campus to trace source of Salmonella contamination with a special focus on antibiotic and disinfectant resistance of the isolates. Salmonella isolates were identified by conventional and molecular techniques. Genetic similarity, antibiotic and disinfectant resistance patterns of the isolates were performed by sequence analyzing, disc diffusion and PCR, respectively. Salmonella contamination was determined from hand (Newport and Infantis), knife handle (Newport) and grilled chicken (Koessen) samples. The identity of the 16S rRNA sequence of two Newport isolates (knife handle and hand) from Canteen 4 and Canteen 6 were found 100% identic. Multidrug resistance (MDR) was observed among all Salmonella isolates with resistance to at least five or more antibiotics. sugE and qacEΔ1 disinfectant genes were determined in 2 and 1 isolate respectively while cross-resistance to antibiotics and disinfectants in three isolates were detected. The results of this study indicate that the food-handlers and food preparation equipments may serve as reservoirs for cross-resistant Salmonella, a potential public health concern. Therefore, periodic training programmes should effectively be implemented for food handlers. Owing to the growing concern that antibiotic resistant mutants could be induced by improper disinfectant use, unnecessary and misuse of disinfectants should be avoided, especially on food contact surfaces.